CRITERIA FOR MULTI AIRPORT SYSTEM DEVELOPMENT IN METROPOLITAN AREA - Surya Apriansyah (Institut Teknologi Dirgantara Adisutjipto, 2021)
Soekarno Hatta International Airport and Halim Perdana Kusuma Airport are located in the Jabodetabek metropolitan area which is the largest area for air transportation users in Indonesia. Along with the increasing number of users of air transportation modes, a multi-airport system is needed to reduce the burden on one airport. The method used is a qualitative analysis method by comparing existing data with data obtained from research to determine a multi-airport criteria. From the results of data processing, it is concluded that the development of a multi-airport system in the Jabodetabek metropolitan area has several criteria, namely airport distance, accessibility, airport management, airport route services, passenger demand as well as government regulations and policies governing the multi-airport systems.